Peculiarities of the Nature and Status of the Russian Presidential Administration: Historical, Political and Legal Overview - Zuykov, Anton Vladimirovich (Journal of History Culture and Art Research, 2018)
The Presidential Administration in the Russian Federation has never been just an adminicular mechanism of the head of state. Unlike its western analogs, it has always possessed an incomparably large resource of power. While presidents were changed, the personal stuff, structure and authorities of this body were also changed, but its central place in the management system of the Russian state remained stable. The Administration of the President of the Russian Federation is an institution, whose legal status does not have a clear legal shape. Not without reason the journalists, as well as lawyers, political scientists and historians sometimes call it the shadow government or the secret order. However, the legal nature of the administration of the President of the Russian Federation is not quite clear. Even the name "Administration" is often misleading: whether the Administration of the President of the Russian Federation may be considered the executive power or the public administration in a wider sense? This and other disputes about the nature of the Presidential Administration of the Russian Federation and its legal status have arisen in the expert community with the beginning of complex work on the constitutional project, and are still ongoing today. In this regard, the author of this article decided to make one of the first attempts in the country to investigate what the Administration of the President of the Russian Federation really is, what are the problems associated with its functioning, and whether there are legal means to resolve them at the present stage. To answer these questions, the author thoroughly analyzes the models and arguments proposed at different stages of the development of the new Russia, and correlates them with the basic constitutional principles.